1996
DOI: 10.1007/bf00311590
|View full text |Cite
|
Sign up to set email alerts
|

Successful utilization of the median sternotomy approach in the management of descending necrotizing mediastinitis: Report of a case

Abstract: We describe herein the case of a patient in whom a median sternotomy was successfully employed for mediastinal drainage in the treatment of descending necrotizing mediastinitis (DNM). Although most reports describe cervical or thoracotomy approaches, our experience strongly suggests that median sternotomy is a satisfactory alternative approach for treatment of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Diffuse DNM-type IIB demanded complete mediastinal drainage with debridement via thoracotomy, and subxiphoidal mediastinal drainage without sternotomy might provide adequate drainage in type IIA DNM. Many authors have reported the advantage of drainage and debridement through more aggressive open surgical approaches in the management of patients with DNM [13][14][15][16]. However, these aggressive approaches may worsen the condition of patients with sepsis and also increase the length of hospital stay, increase morbidity, and mortality.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Diffuse DNM-type IIB demanded complete mediastinal drainage with debridement via thoracotomy, and subxiphoidal mediastinal drainage without sternotomy might provide adequate drainage in type IIA DNM. Many authors have reported the advantage of drainage and debridement through more aggressive open surgical approaches in the management of patients with DNM [13][14][15][16]. However, these aggressive approaches may worsen the condition of patients with sepsis and also increase the length of hospital stay, increase morbidity, and mortality.…”
Section: Discussionmentioning
confidence: 95%
“…However, these aggressive approaches may worsen the condition of patients with sepsis and also increase the length of hospital stay, increase morbidity, and mortality. Particularly, because median sternotomy [15] or clamshell incisions [16] may cause subsequent osteomyelitis and dehiscence of sternum, these procedures seem detrimental in patients with DNM.…”
Section: Discussionmentioning
confidence: 99%
“…Case 2 was classifi ed as type IIA. Concerning the approach for type IIA, a subxiphoid approach, 3 a median sternotomy, 9 and a thoracotomy 4,10 have been described, but the anterior approach of costal cartilage resection, which we performed in case 2, has not previously been reported. This approach was suffi cient for anterior mediastinal drainage and is a minimally invasive method.…”
Section: Discussionmentioning
confidence: 91%
“…However, some authors [ 16 , 17 ] preferred sternotomy or clamshell incision for DNM because they ensure good access to the anterior mediastinum and to both thoracic cavities; in a single-center series published in 2012 [ 18 ], 16 patients with diffuse DNM were surgically treated by median sternotomy ( n = 8) or the clamshell ( n = 8) approach, with a mortality rate of 12.5% (2/16; the first for MOF 48 h after clamshell incision and the second for ARDS 4 months later, after several redo-clamshell operations). Although the authors did not correlate the cause of the exitus with the technical choice of surgery, we consider this approach at risk for osteomyelitis and dehiscence of the sternum; furthermore, it seems not so suitable for draining the infero-posterior mediastinum collections, even when performed in single-lung ventilation.…”
Section: Discussionmentioning
confidence: 99%